PESAN DAKWAH DALAM FILM â€œGAGAL TAâ€™ARUFâ€ DI CHANNEL YOUTUBE TELADAN CINEMA Edisi 15 Desember 2020 - Megasari, Andrina; Anwari, Anwari (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
Along with the development of today's times and technology, films have become one of the most effective mass communication media. The purpose of this study was to determine the meaning of the message sign of da'wah and the meaning of the message of da'wah contained in the film Failed to Ta'aruf. To answer the two problem formulations, the researcher used a qualitative approach. While the method used is the semiotic method of Charles Sanders Pierce. In this study, it is concluded that the signs contained in the film Fail to Ta'aruf are relevant to the theory developed by Charles Sanders Pierce. Charles Sanders Pierce classifies signs into icons, indexes, and symbols. Where the meaning of the sign is an unforgettable part. And the meaning of the message of da'wah in the film Failed to Ta'aruf is in the category of creed, namely istigfar. Sharia categories are such as ta'aruf, marriage, and congregational prayers. The moral category is being grateful, greeting and answering greetings, being responsible, not having bad prejudice or suudzon towards others, not expecting humans, and being devoted to both parents. Keywords: Film Semiotics, Meaning of Da'wah Messages.